2014
DOI: 10.7196/samj.8423
|View full text |Cite
|
Sign up to set email alerts
|

South African Menopause Society revised consensus position statement on menopausal hormone therapy, 2014

Abstract: The South African Menopause Society (SAMS) consensus position statement on menopausal hormone therapy (HT) 2014 is a revision of the SAMS Council consensus statement on menopausal HT published in the SAMJ in May 2007. Information presented in the previous statement has been re-evaluated and new evidence has been incorporated. While the recommendations pertaining to HT remain similar to those in the previous statement, the 2014 revision includes a wider range of clinical benefits for HT, the inclusion of non-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 61 publications
0
21
0
2
Order By: Relevance
“…Progesterone has both sedative and anxiolytic effects, stimulating benzodiazipine receptors, which play an important role in sleep cycle [32]. However, direct evidence for this theory could not be found in the literature.…”
Section: Progesteronementioning
confidence: 99%
See 1 more Smart Citation
“…Progesterone has both sedative and anxiolytic effects, stimulating benzodiazipine receptors, which play an important role in sleep cycle [32]. However, direct evidence for this theory could not be found in the literature.…”
Section: Progesteronementioning
confidence: 99%
“…Studies by Guidozzi et al showed a significant correlation between depression and sleep related disorders [32]. Thus, treatment of both depression and sleep disturbance is essential regardless of age or menopause status [26].…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…17β estradiol (E2) is the main contributor of the estrogen-dependent processes in peripheral tissues regulating bone growth and early atherogenesis (13). Moreover, it is the main determinant for the proliferation of breast cancer cells in vivo (14,15). In an attempt to avoid the risks, the search for alternative therapy is justified, but the belief that "natural" alternatives have no adverse effect is mistaken (16).…”
Section: Introductionmentioning
confidence: 99%
“…The South African Menopause Society 2014 consensus position state ment on menopausal hormone therapy [12] is a revision of their state ment published in the SAMJ of May 2007. [13] The revised statement emphasises that commencing hormone therapy during the 'therapeutic window of opportunity' maximises the benefit-to-risk profile of therapy in symptomatic menopausal women.…”
Section: Menopausal Hormone Therapymentioning
confidence: 99%